1992
DOI: 10.1017/s0272263100010822
|View full text |Cite
|
Sign up to set email alerts
|

Integrative Motivation, Induced Anxiety, and Language Learning in a Controlled Environment

Abstract: This study examines the effects of both integrative motivation and anxiety on computerized vocabulary acquisition using a laboratory analog procedure as a microcosm of second language learning. An attempt was made to induce anxiety in one group of subjects by videotaping them while learning. Individual differences in integrative motivation were measured by aggregating relevant scales. Subjects higher in integrative motivation showed superior vocabulary acquisition and tended to initiate a translation more quic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
80
1
4

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(92 citation statements)
references
References 25 publications
7
80
1
4
Order By: Relevance
“…Namely, all the subscale scores barely exceeded their scale midpoints (36,21, and 6 for the FLCAS1, the FLCAS2, and the FLCAS3, respectively). This lends further support to the result of the FLCAS data that nearly a third of the respondents felt anxious in English class, feared being negatively evaluated, and were apprehensive about both speaking and tests, as found in Liu and Jackson"s (2008) study and many others in various contexts (Gardner & MacIntyre, 1992;Horwitz et al, 1986;Horwitz, 2001;Liu, 2006Liu, , 2007.…”
Section: A Broad Profile Of Foreign Language Classroom Anxietysupporting
confidence: 80%
“…Namely, all the subscale scores barely exceeded their scale midpoints (36,21, and 6 for the FLCAS1, the FLCAS2, and the FLCAS3, respectively). This lends further support to the result of the FLCAS data that nearly a third of the respondents felt anxious in English class, feared being negatively evaluated, and were apprehensive about both speaking and tests, as found in Liu and Jackson"s (2008) study and many others in various contexts (Gardner & MacIntyre, 1992;Horwitz et al, 1986;Horwitz, 2001;Liu, 2006Liu, , 2007.…”
Section: A Broad Profile Of Foreign Language Classroom Anxietysupporting
confidence: 80%
“…We share Rodríguez and Abreu's (2003, p. 371) idea that complex relationships may be established between FL anxiety and different affective, cognitive and demographic aspects such as learners' aptitude, motivation, and culture. Sufficient evidence exists to affirm that motivation and anxiety have opposite effects on FL learning (Gardner, Day and MacIntyre, 1992;Gardner and MacIntyre, 1993;MacInyre, 1995;MacIntyre, 2002;Matsuda and Gobel, 2004). We believe that the voluntary choosing of English implies a high level of motivation, which presumably will condition both learning quality and anxiety levels.…”
Section: Do Pre-service Primary English Teachers Have Lower Anxiety Lmentioning
confidence: 85%
“…The authors noted that participants' mean language anxiety score was lower than the scores reported in other studies (see below). Research has demonstrated that motivation and anxiety have opposite effects on FL learning (Gardner, Day and MacIntyre, 1992). Motivation encourages learners in their FL learning whereas anxiety interferes with it.…”
Section: Introductionmentioning
confidence: 99%
“…While some scholars believe that instrumental motivation facilitates language learning (e.g., see Idawati, 2010;Lukmani, 1972;Warden & Lin, 2000), others believe that integrative motivation is an asset in language learning (Gardner, Day & Maclntyre, 1992;Sadighi & Maghsudi;Strong, 1984). Moreover, some research studies have also revealed that both integrative and instrumental motivation facilitate learning (e.g., see Dörnyei, 1990;Gardner & MacIntyre, 1991) Schmidt (1995 postulated that motivation and some other affective factors play key roles in learners' pragmatic development.…”
Section: Introductionmentioning
confidence: 99%